EFFECTIVE STRATEGIES FOR IMPROVING SPEAKING PROFICIENCY (Konferensiyalar | Conferences, 2024)
Many students master the fine points of English grammar but find themselves at a loss when it comes to actually having a conversation with native speakers. In reality, the only way to develop fluency in speaking is by huge amounts of listening, and then practicing. The following are a few tips for improving English speaking skills. Don’t forget that listening is the foundation for speaking! When you also want to practice speaking, here are some suggestions for how to improve English speaking skills.